Neutralização de carbono por meio de inventário das emissões de gases de efeito estufa a partir do planejamento institucional da UFU - Gonzaga, Eunir Augusto Reis (2016)
The anthropic actions after the Industrial Revolution began to consider the environment as a space supplier of natural resources to the Capital. It suppressed the native vegetation of different biomes, replacing the space for cities, industry, agriculture, pastures, causing air pollution, which directly impacted in the current context of climate change. In this sense, it was noticed that there was a lack of public records inventories, containing greenhouse gases from UFU. The purpose of the study was to identify the institutional planning indicators for stationary combustion, mobile combustion, fugitive emissions, agricultural activities, solid waste and wastewater, for Scope 1 and acquisition of electricity and thermal energy for Scope 2 using the tool intersectoral GRI. We chose the methodology GHG Protocol for being an internationally accepted standard. The main results were the emissions of equivalent CO2, proposing neutralization through the planting of native plants of the Cerrado Biome. The inventory can not only enable the implementation of measures for mitigation and compensation, as well as optimize public spending, contributing to the Environmental Agenda of Public Administration (A3P).